PALLIATIVE CARE GUIDELINES FOR PATIENTS UNDERGOING HEMATOPOIETIC STEM CELL TRANSPLANTATION - Vivian Maria Reksua; Maria Cristina Paganini (Universidade Federal do Paraná, 2015)
Qualitative study aimed to propose palliative care guidelines for patients undergoing hematopoietic stem cell transplantation. The setting was a teaching hospital in Curitiba, state of Paraná. The study was conducted in 2014 in two stages: the first, exploratory stage, with semi-structured interviews with 12 nurses. Three topics emerged from content analysis: 1) Perception of palliative care in the workplace; 2) Sense assigned to palliative care; 3) Professional-family interaction in palliative care. In the second stage palliative care guidelines were proposed and approved in meetings with nurses. The definition of palliative care guidelines may facilitate and improve the palliative care delivered by multidisciplinary teams, with a positive impact on the quality of life of patients with a terminal disease and their families.